Institute of Metals Division - Effect of Si and Al on the Stability of Certainsigma Phases - K. P. Gupta; N. S. Rajan; P. A. Beck (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1961)
By determining the a phase boundaries in the following ternary systems: V-Fe-Si (at 1175oC), V-Co-Si (at 1175°C), V-Ni-Si (at 1175oC), Cr-Mn-Si (at 1000°C), Cr-Co-Si (at 1175°C), Cr-Ni-Si (at 1175°C), V-Fe-A1 (at 1175°C) and Cr-Co-A1 (at 1175°C), it was found that Si exerts a stabilizing effect on these a phases, while A1 tends to destabilize them. Si atoms in solid solution occupy sites D in the a structure, The co/ao ratio increases with increasing Si-, Mn- or Fe-content. The volume of the unit cell decreases with increasing Si-content. THE stabilization of certain metal silicides (the Nowotny phases) by the addition of relatively small